The core of the massive cluster merger MACS J0417.5−1154 as seen by VLT/MUSE. Issue 3 (7th December 2018) - Jauzac, Mathilde; Mahler, Guillaume; Edge, Alastair C; Sharon, Keren; Gillman, Steven; Ebeling, Harald; Harvey, David; Richard, Johan; Hamer, Stephen L; Fumagalli, Michele; Mark Swinbank, A; Kneib, Jean-Paul; et al.
ABSTRACT: We present a multiwavelength analysis of the core of the massive galaxy cluster MACS J0417.5−1154 (z = 0.441). Our analysis takes advantage of Very Large Telescope/Multi-Unit Spectroscopic Explorer observations which allow the spectroscopic confirmation of three strongly lensed systems. System #1, nicknamed The Doughnut, consists of three images of a complex ring galaxy atz = 0.8718 and a fourth, partial and radial image close to the brightest cluster galaxy (BCG) only discernible thanks to its strong [O ii ] line emission. The best-fitting mass model (rms of 0.38 arcsec) yields a two-dimensional enclosed mass ofM(R 200 kpc) = (1.77± 0.03)× 10^14 M_ and almost perfect alignment between the peaks of the BCG light and the dark matter of (0.5 ± 0.5) arcsec. We observe a significant misalignment when system #1 radial image is omitted. The result serves as an important caveat for studies of BCG–dark-matter offsets in galaxy clusters. Using Chandra to map the intracluster gas, we observe an offset between gas and dark matter of (1.7 ± 0.5) arcsec, and excellent alignment of the X-ray peak with the location of optical emission line associated with the BCG. We interpret all observational evidences in the framework of ongoing cluster merger activity, noting specifically that the coincidence between the gas and optical line peaks may be evidence of dense, cold gas cooled directly from the intracluster gas. Finally, we measure the surface area, σμ, above a given magnification factor μ, a metric to estimate the lensing power of a lens, σ(μ > 3) = 0.22 arcmin 2, which confirms MACS J0417 as an efficient gravitational lens.